Role of EP4 factor in paediatric type 1 diabetes mellitus: a comprehensive review focusing on the honeymoon period - Forough Taheri; Nekoo Panahi; Aida Vahidi; Mojgan Asadi; Mahsa M. Amoli; Naieme Goharifar (Pediatric Endocrinology, Diabetes and Metabolism)
The partial clinical recovery phase (PCRP), or “honeymoon period”, is a temporary and partial restoration of b-cell function in patients with type 1 diabetes mellitus (T1DM), in which the immune system attacks and destroys insulin-producing b-cells. The underlying causes of PCRP are not fully understood, but they are believed to involve a combination of genetic and environmental factors. Recent research has suggested a potential link between a specific allele of the prostaglandin receptor EP4 (PTGER4) and the modulation of remission in individuals with T1DM. This review aims to provide an overview of current scientific findings on the biological functions and role of the EP4 receptor in T1DM, with a particular focus on its involvement in the PCR phase. It provides a comprehensive understanding of the mechanisms underlying PCRP, which can lead to the development of more effective treatment strategies for preserving b-cell function and prolonging the PCRP. The identification of specific biomarkers associated with the PCRP and the EP4 receptor enables early identification of individuals at lower risk of long-term complications, facilitating targeted interventions and personalised treatment approaches.